The nature of frontier orbitals under systematic ligand exchange in (pseudo-)octahedral Fe(ii) complexes. Issue 44 (13th September 2018) - Jay, Raphael M.; Eckert, Sebastian; Fondell, Mattis; Miedema, Piter S.; Norell, Jesper; Pietzsch, Annette; Quevedo, Wilson; Niskanen, Johannes; Kunnus, Kristjan; Föhlisch, Alexander
Abstract : The impact of ligand substitution on metal-ligand covalency and the valence excited state landscape is investigated using resonant inelastic soft X-ray scattering. Abstract : Understanding and controlling properties of transition metal complexes is a crucial step towards tailoring materials for sustainable energy applications. In a systematic approach, we use resonant inelastic X-ray scattering to study the influence of ligand substitution on the valence electronic structure around an aqueous iron(ii ) center. Exchanging cyanide with 2-2′-bipyridine ligands reshapes frontier orbitals in a way that reduces metal 3d charge delocalization onto the ligands. This net decrease of metal–ligand covalency results in lower metal-centered excited state energies in agreement with previously reported excited state dynamics. Furthermore, traces of solvent-effects were found indicating a varying interaction strength of the solvent with ligands of different character. Our results demonstrate how ligand exchange can be exploited to shape frontier orbitals of transition metal complexes in solution-phase chemistry; insights upon which future efforts can built when tailoring the functionality of photoactive systems for light-harvesting applications.